Sensing Infrared Photons at Room Temperature: From Bulk Materials to Atomic Layers - Wang, Peng; Xia, Hui; Li, Qing; Wang, Fang; Zhang, Lili; Li, Tianxin; Martyniuk, Piotr; Rogalski, Antoni; Hu, Weida (Small (Weinheim an der Bergstrasse, Germany), 2019)
Room‐temperature operating means a profound reduction of volume, power consumption, and cost for infrared (IR) photodetectors, which promise a wide range of applications in both military and civilian areas, including individual soldier equipment, automatic driving, etc. Inspired by this fact, since the beginning of 1990s, great efforts have been made in the development of uncooled thermal detectors. During the last two decades, similar efforts have been devoted using IR photon detectors, especially based on photovoltaic effects. Herein, the proven technologies, which have been commercialized with a large format, like InGaAs/InP pin diodes, InAsSb barrier detectors, and high‐operating‐temperature HgCdTe devices, are reviewed. The newly developed technology is emphasized, which has shown unique superiority in detecting mid‐wavelength and long‐wavelength IR signals, such as quantum cascade photodetectors. Finally, brand‐new concept devices based on 2D materials are introduced, which are demonstrated to provide additional degrees of freedom in designing and fabricating room‐temperature IR devices, for example, the construction of multi‐heterojunctions without introducing lattice strain, the convenient integration of optical waveguides and electronic gratings. All information provided here aims to supply a full view of the progress and challenges of room‐temperature IR detectors. Room‐temperature operating means a profound reduction of volume, power consumption, and cost for infrared photodetectors. Infrared photon detectors show broad development prospects with theoretically superior performance limits at room temperature, and progress from bulk to atomic layers, which promise a wide range of applications in many aspects.